Comparative analysis of validation of compassion fatigue short scale and Professional Quality of Life Scale (ProQOL) in China under COVID-19 pandemic - Yutong Zhang (2021)
Objective: To compare and analyze different existing compassion fatigue (CF) scales, and to test reliability and validity to find out a more suitable evaluation tool of CF for Chinese front-line medical staff. Method: With a sample of 252 Chinese clinicians (doctors and nurses), this study compared the validation of the two most used CF scales, Compassion Fatigue Short Scale (CF-Short Scale) and Professional Quality of Life Scale (ProQOL) in Chinese healthcare setting. Exploratory factor analysis, correlation analysis, and Cronbach's α were employed to examine the reliability and validity of the Chinese version of the CF scale by front-line clinical nurses and doctors. Lastly, One-way ANOVA test was conducted to examine and compare the CF scores of the medical staff with different characteristics. Finding: The Compassion Fatigue Short Scale included two factors, explaining totally 64.273％of the total variance, and Cronbach's α of C-CF Short Scale = 0.918, Job Burnout (JB) = 0.892, and Secondary Trauma (ST) = 0.909. The ProQOL (C-ProQOL) Scale also had a good internal consistency, with Cronbach's α of Compassion Satisfaction (CS) = 0.925, Secondary Trauma (ST) = 0.925, and Burnout (BO)= 0.705. However, the construct validity of C-ProQOL Scale was unsatisfactory with some problematic items. The CF scores among medical staff was at a medium level and differed significantly by the number of hours worked, the number of night shifts, and other characteristics of the medical staff. Conclusion: The C-CF Short Scale has better applicability that can be used as a reliable CF measurement for Chinese medical staff.